2002
DOI: 10.1108/eb028956
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Intelligence in the Workplace: Exploring Its Effects on Occupational Stress and Organizational Commitment

Abstract: The purpose of the present study is to explore the relationship between emotional intelligence and sources of occupational stress and outcomes on a sample of professionals in mental health institutions. A total of 212 participants were administered the Emotional Intelligence Questionnaire as well as the Organizational Stress Screening Tool (ASSET), a new organizational screening tool, which measures workplace stress. The results were in the expected direction showing a negative correlation between emotional in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
173
0
21

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(206 citation statements)
references
References 18 publications
12
173
0
21
Order By: Relevance
“…On the other hand, EI also explored a significant positive impact on organizational commitment. This finding is also consistent with previous studies (Güleryüz et al, 2008;Nikolaou & Tsaousis, 2002), indicating that employees who are emotionally intelligent will demonstrate high level of organizational commitment. It is inevitable to increase organizational commitment by enhancing EI of nurses.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…On the other hand, EI also explored a significant positive impact on organizational commitment. This finding is also consistent with previous studies (Güleryüz et al, 2008;Nikolaou & Tsaousis, 2002), indicating that employees who are emotionally intelligent will demonstrate high level of organizational commitment. It is inevitable to increase organizational commitment by enhancing EI of nurses.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…To summarize, a limited studies found the relationship between EI and organizational commitment (Güleryüz et al, 2008;Nikolaou & Tsaousis, 2002) and EI and MH (Mohammadyfar et al, 2009;Slaski & Cartwright, 2002). The present study investigates the mediating effect of organizational commitment between EI and MH of Pakistani nurses.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Así, las personas con una disposición emocional positiva comprenden las emociones originadas en su entorno, analizan sus causas y consecuencias y saben regular estas emociones con estrategias ajustadas (Salovey, Mayer y Caruso, 2002). Otros estudios apuntan que estas habilidades ayudan a una mejor percepción de autoeficacia y un mejor afrontamiento de los conflictos acaecidos en el entorno laboral (Bar-On, Brown, Kirkcaldy y Thome, 2000;Durán, Extremera y Rey, 2004;Limonero, Tomás Sábado, Fernández-Castro y Gómez-Benito, 2004;Nikolaou y Tsaousis, 2002).…”
Section: Relaciones Entre Afectividad Y Rendimiento Académicounclassified
“…Among the areas with the strongest connections to EI is developmental, educational, clinical and counselling, industrial and organizational psychology. Hence, characteristic or ability EI were related to life success (Bar-On, 2001;Goleman, 1995), life satisfaction and well-being (Martinez-Pons, 1997;Bar-On, 2002;Palmer et al, 2002), individual performance (Lam & Kirby, 2002), interpersonal relationships (Fitness, 2001;Flury & Ickes, 2001), academic achievement ( Van der Zee et al, 2002;Parker et al, 2004), vocational stress (Bar-On et al, 2000;Nikolaou & Tsaousis, 2002;Slaski & Cartwright, 2002), job success and performance (Dulewicz & Higgs, 1998;Vakola et al, 2004), leadership (Cooper & Sawaf, 1997;Palmer et al, 2000) and more. Several other authors (e.g.…”
Section: Introductionmentioning
confidence: 99%